Efektivitas Diplomasi Lingkungan Kota Bandung–Kota Kawasaki dalam Mengoptimalkan Program Green City Tahun 2024–2025: Studi Kasus Alih Teknologi Pengelolaan Lingkungan - Fadhillah Putri Sudrajat; Siva Yunika; Salsabila Aulia Emelda; Desi Qodriah Syahfitri; Epa Fauziah; Diyah Pitaloka Rizky (Jurnal Ilmu Sosial dan Humaniora, 2026)
Facing the challenges of climate change and increasing urbanization pressures, the Bandung City Government has adopted the green city concept as part of its sustainable development strategy. In its implementation, Bandung utilizes environmental paradiplomacy through cooperation with Kawasaki City, Japan, focusing on technology transfer in waste management and environmental sectors. However, the effectiveness of translating this technological support into local policies remains constrained by bureaucratic obstacles and leadership sustainability issues, resulting in a gap between international technical assistance and tangible local impacts. This study employs a qualitative approach with an instrumental case study to analyze the environmental paradiplomacy strategies implemented by the Bandung City Government in optimizing technology transfer from Kawasaki City during the 2024–2025 period. The research focuses on three main aspects: the role of key actors in the cooperation process, the mechanisms of technology transfer, and the internalization of diplomatic outcomes into green city policies. The findings are expected to contribute to the literature on environmental paradiplomacy at the municipal level, particularly in the context of foreign technology adoption, and to provide strategic recommendations for enhancing the effectiveness and sustainability of international cooperation in green city development.